Gas exchange characteristics and Leaf Chlorophyll content of two local hosts infected by Jarum Mas (Striga asiatica). - Ramlan, Mohd Fauzi; Tengku Muda Mohamed, Mahmud; Hassan, Siti Aishah (Malaysian Society of Applied Biology, 1998)
The effect of Jarum Mas (Striga asiatica), a parasite, on the gas exchange capacity and leaf chlorophyll content of two local grasses was studied. Infection by S. asiatica reduced the host photosynthetic capacity by reducing the apparenl quantum yield used for CO, fixation. In Ischaemum indicum, lower photosynthesis rates were also due to the reduction of RuBP-carboxylase capacity and the RuBP-carboxylase regeneration capacity of the host.